Chemometric Assisted Spectrophotometric Method Development for Evaluation of Torsemide and Eplerenone in their Combined Tablet Dosage Forms - A, Madhuri; Patel, Dipti (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: In a present work two drugs Torsemide and Eplerenone were estimated from their combined tablet dosage forms by applying chemometric assisted spectrophotometric method. Methods: The methods are based on chemometrics a (multivariate) method which includes classical least square (CLS) and inverse least square (ILS). These methods were employed for simultaneous determination of Torsemide and Eplerenone in tablet dosage forms without any prior separation of components. For these methods the overlapping spectra of two drugs not subjected any conversions. The data processing of chemometric was accomplished by using software named Chemometrics Toolbox 3.02 which is associated with MATLAB 6 and excel. Results: The results obtained from CLS and ILS methods were compared statistically. These chemometric methods were applied for the determination of these two drugs in their marketed tablet dosage form without any prior separation procedure of the drugs. The mean percent recoveries and values of relative standard deviation for these two methods were found to be 99.72/0.536 for Torsemide and 100.06/0.384 for Eplerenone. Conclusion: The two chemometric methods developed can be successfully applied for the quantitative estimation of drugs from their dosage form.
Keywords: Spectrophotometry; Chemometrics; Torsemide; Eplerenone; Classical least; square method; Inverse least square method; Root mean square error of prediction